Increasing Onshore Oil Production: An Unexpected Explosion in Trauma Patients - Urban, Dakota M.; Ward, Jeanette G.; Helmer, Stephen D.; Cook, Alan D.; Haan, James M. (Kansas Journal of Medicine, 2019)
Introduction. Few data currently exist which are focused on type and severity of onshore oil extraction-related injuries. The purpose of this study was to evaluate injury patterns among onshore oil field operations. Methods. A retrospective review was conducted of all trauma patients aged 18 and older with an onshore oil field-related injury admitted to an American College of Surgeons-verified level 1 trauma center between January 1, 2003 and June 30, 2012. Data collected included demographics, injury severity and details, hospital outcomes, and disposition. Results. A total of 66 patients met inclusion criteria. All patients were male, of which the majority were Caucasian (81.8%, n = 54) with an average age of 36.5 ± 11.8 years, injury severity score of 9.4 ± 8.9, and Glasgow Coma Scale score of 13.8 ± 3.4. Extremity injuries were the most common (43.9%, n = 29), and most were the result of being struck by an object (40.9%, n = 27). Approximately onethird of patients (34.8%, n = 23) were admitted to the intensive care unit. Nine patients (13.6%) required mechanical ventilation while 27 (40.9%) underwent operative treatment. The average hospital length of stay was 5.8 ± 16.6 days, and most patients (78.8%, n = 52) were discharged home. Four patients suffered permanent disabilities, and there were two deaths. Conclusions. Increased domestic onshore oil production inevitably will result in higher numbers of oil field-related traumas. By focusing on employees who are at the greatest risk for injuries and by targeting the main causes of injuries, training programs can lead to a decrease in injury incidence. Kans J Med 2018;11(2):34-37.